MORPHOLOGICAL AND PHYSIOLOGICAL CHARACTERISTICS OF SHOOTS MULTIPLICATED AGAPANTHUS SHOOTS IN DIFFERENTS LIGHT INTENSITY AND SUCROSE CONCENTRATIONS - FOGAÇA, Luciana Alves; DORTZBACH, Denilson; ALVES, Antonio Carlos; PEDROTTI, Enio Luiz (Scientia Agraria, 2007)
Agapanthus umbellatus var. minor is an ornamental plant a lot used as lip in gardens, its can used as cut flower. Your propagation is traditionally made the dividing the roots, what limits your propagation in large scale, with use of the micropropagation it is possible to enlarge the planting with seedlings of high quality. However, this process induces a great number of changes anatomical, morphologic and physiologic that they are decisive in the morphogenesis, in the growth and in the development of the plants in vitro. This work aimed at studying the morphological and physiological traits of shoots of Agapanthus umbellatus var. minor multiplicated. It’s used explants shift of the shoots obtained in vitro and inoculated in medium MS with concentrations sucrose differents ((0,0; 1,5; 3,0 e 4,5%) and two light intensity (70 e 140 mM m-2 s-1), totalyzing eight treatments, in factorial 4 x 2, the design utilized was completely randomized. The results indicated that the environment conditions, mainly light and sucrose concentration of the culture medium, influenced the development and the growth of shoots. It was observed that the absence of sucrose, even in the highest level light intensity, didn’t at estimulate the photossyntesis the shoots. There was variation in results obtained; however advice the concentration of 30 g L-1 of sucrose and 70 mM m-2 s-1 of light for phase of multiplication of Agapantho, this combination has proposed the larger production of shoots and concentration of chlorophyll a, b and total.